Ferroelastic phase transition in [(C2H5)4N][(CH3)4N]MnBr4. (3rd June 2017) - Szklarz, P.; Ingram, A.; Czapla, Z.; Górecki, C.; Szafrański, M.
ABSTRACT: Crystal growth, DSC, X-ray structural studies, optical observation and dielectric studies for a new hybrid organic–inorganic [(C2 H5 )4 N][(CH3 )4 N]MnBr4 crystal are presented. The studies revealed reversible first-order phase transition of a ferroelastic type at 484/482 K on a heating and cooling run, respectively. Unusual feature of this transition is reduction of symmetry on heating run. At room temperature phase the crystal is tetragonal with the space groupP 4 ¯ 2 1 m and above the phase transition temperature it is orthorhombic with the space groupP 2 1 2 1 2 . The symmetry change at the transition fulfills the reverse group–subgroup relation. Above the phase transition, the ferroelastic domain structure consistent with Aizu's species4 ¯ 2 m F 222 was revealed by polarized microscopy observation. The phase transition exhibiting such features has not been presented so far. Dielectric studies revealed a significant increase of losses connected with conductivity. The temperature dependence of conductivity and conductivity relaxation time fulfill the Arrhenius relation and activation energies are estimated.